B-cells in systemic sclerosis. Issue 6 (November 2015) - Wu, Minghua; Mohan, Chandra
<x xml:space="preserve">Abstract</x> Purpose of review This review aims to summarize current evidence for a role of B-cells in the pathogenesis of systemic sclerosis (SSc) from genetics to phenotypes, with an emphasis on recent insights. Recent findings Multiple genomic analyses have associated several B-cell signalling genes with SSc. Moreover, interesting B-cell subset alterations and activation/memory marker changes have also been documented in SSc. Co-cultures of blood B-cells with dermal fibroblasts isolated from SSc patients demonstrated the induction of collagen, interleukin (IL)-6, transforming growth factor (TGF)-β1, IL-1β and chemokine (c-c motif) ligand 2 (CCL2) in the fibroblasts, following potential B-cell cues delivered to the fibroblasts. Plasma cell gene signatures were elevated in SSc patients' blood, and highly correlated with collagen gene expression. Finally, anti-CD20 B-cell depletion therapy not only improved skin disease but also preserved interstitial lung disease in early diffuse cutaneous disease. Summary Thus, there is resounding evidence that B-cells play a pivotal role in pathogenesis of SSc. However, the molecular pathways through which B-cells may direct fibroblast function, SSc disease development and progression remain unclear, and warrant further study.